2019
DOI: 10.1017/s0144686x1900059x
|View full text |Cite
|
Sign up to set email alerts
|

Filial expectation among Chinese immigrants in the United States of America: a cohort comparison

Abstract: Relying on two unique data-sets on Chinese older immigrants (N = 3,157) and younger immigrants with ageing parents (N = 469) in Chicago, this study compared the level of filial expectation among the two groups and examined the predictors and mental health implications of having high filial expectation among each group. Results of t-tests, logistic regression and negative binominal analyses showed that, regardless of socio-demographic variables, acculturation, physical health and family relations, Chinese adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Among the most enduring cultural beliefs of this population is the traditional Confucian ideal of filial piety—the expectation that children obey, respect, and serve their older parents. This norm is deeply rooted in values of familism and the virtue of maintaining strong intergenerational solidarity, which has been found to be positively related to the psychological wellbeing of older Chinese parents (Dong et al, 2012a; Dong et al, 2016; Guo et al, 2019; Liu et al, 2019). However, filial piety is malleable following the social dislocation caused by migration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the most enduring cultural beliefs of this population is the traditional Confucian ideal of filial piety—the expectation that children obey, respect, and serve their older parents. This norm is deeply rooted in values of familism and the virtue of maintaining strong intergenerational solidarity, which has been found to be positively related to the psychological wellbeing of older Chinese parents (Dong et al, 2012a; Dong et al, 2016; Guo et al, 2019; Liu et al, 2019). However, filial piety is malleable following the social dislocation caused by migration.…”
Section: Introductionmentioning
confidence: 99%
“…However, older immigrants in the United States, in comparison to older nonimmigrants, tend to experience worse psychological states due, in part, to challenges of adapting to an unfamiliar social, cultural, and linguistic environment (Gonzalez et al, 2001; Lum & Vanderaa, 2010). Moreover, Chinese-American elders demonstrate negative psychological outcomes with a slow rate of acculturation to Western society and social disconnection from its institutions (Chen et al, 2018; Dong et al, 2012a; Guo et al, 2019; Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differing definitions and age limits in were present in the studies reviewed. While many articles used 65 years or older as their inclusion criteria, others selected a lower age, still categorizing the age as the threshold for ‘older adult.’ For example, Cofie et al [ 51 ], Zhang and Zhan [ 38 ], Nandan [ 48 ], and Gautam et al [ 52 ], included those 50 and older; while Guo et al [ 53 ], Lee and Eaton [ 54 ], Sohng et al [ 55 ], and Aroian and Vander [ 56 ], included those 60 and older. This creates concerns when comparing studies, especially when assessing health insurance, as one needs to be at least 65 to qualify for Medicare unless qualifying via disability status or in few other conditions [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Daphna and Merril's (2006) study found filial norms not only differ by gender, generation and historical era, but they also change across the adult lifespan. The study by M Guo et al (2020) of Chinese older immigrants and younger immigrants with ageing parents demonstrated that Chinese older immigrants who had less education, lower levels of acculturation, poorer health and closer relationships with children reported higher filial expectation. Finally, the study did not reveal significant differences between older immigrants from different home societies, e.g.…”
Section: Discussionmentioning
confidence: 99%